2015
DOI: 10.3892/ijmm.2015.2285
|View full text |Cite
|
Sign up to set email alerts
|

Asparaginase treatment side-effects may be due to genes with homopolymeric Asn codons (Review-Hypothesis)

Abstract: The present treatment of childhood T-cell leukemias involves the systemic administration of prokary-otic L-asparaginase (ASNase), which depletes plasma Asparagine (Asn) and inhibits protein synthesis. The mechanism of therapeutic action of ASNase is poorly understood, as are the etiologies of the side-effects incurred by treatment. Protein expression from genes bearing Asn homopolymeric coding regions (N-hCR) may be particularly susceptible to Asn level fluctuation. In mammals, N-hCR are rare, short and conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 388 publications
(364 reference statements)
1
8
0
Order By: Relevance
“…2019) while lower levels of circulating Asn are associated with increased BMI, IR, and HG (Banerji, 2015;Ottosson et al, 2018). Consistent with these findings, we found a decrease in the levels of Asn in obese T2DM compared to the obese and the lean groups, while the levels of Gln and His were lowered more in the obese than the obese T2DM patients.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…2019) while lower levels of circulating Asn are associated with increased BMI, IR, and HG (Banerji, 2015;Ottosson et al, 2018). Consistent with these findings, we found a decrease in the levels of Asn in obese T2DM compared to the obese and the lean groups, while the levels of Gln and His were lowered more in the obese than the obese T2DM patients.…”
Section: Discussionsupporting
confidence: 86%
“…A high-fat diet in animal models reduced the levels of Gln and Asn (gluconeogenic amino acids) and 4,6-dihydroxyquinoline ( Liu et al, 2017 ). Higher levels of Gln and His (suppressor of hepatic gluconeogenesis) are known to be significantly associated with a lower risk for incident T2DM ( Kimura et al, 2013 ; Chen et al, 2019 ) while lower levels of circulating Asn are associated with increased BMI, IR, and HG ( Banerji, 2015 ; Ottosson et al, 2018 ). Consistent with these findings, we found a decrease in the levels of Asn in obese T2DM compared to the obese and the lean groups, while the levels of Gln and His were lowered more in the obese than the obese T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lower levels of methionine increase the generation of hydrogen sulphide, which was reported to improve the metabolic function of adipose tissue, liver and β cells . The amino acids arginine and asparagine are elevated in plant proteins (eg, legumes) and arginine may improve insulin sensitivity by increasing microvascular function via nitric oxide production, while asparagine shows tight links with glucose homeostasis …”
Section: Introductionmentioning
confidence: 99%
“…19 The amino acids arginine and asparagine are elevated in plant proteins (eg, legumes) 20 and arginine may improve insulin sensitivity by increasing microvascular function via nitric oxide production, 21 while asparagine shows tight links with glucose homeostasis. 22 The impact of protein consumption on kidney function is controversial and meta-analyses reported that higher amounts of protein either did not affect or deteriorated renal function. 23,24 To our knowledge there are only two studies comparing effects of AP with PP meals on renal and glycaemic variables in people with T2DM.…”
mentioning
confidence: 99%
“…Development of pancreatitis results in termination of chemotherapy, allowing for cancer progression; consequently, patients diagnosed with ALL who develop AAP are at greater risk for death (28,44,61). Genetic predispositions are hypothesized to play a role (5,28,41), but evidence to establish causation is lacking. A deeper understanding of the molecular basis for AAP will provide an important guide to improve patient treatment through the development of evidence-based guidelines for prevention and management.…”
mentioning
confidence: 96%